USING ART AS THERAPY FOR YOUNG CHILDREN EXPERIENCING TRAUMATIC EVENTS - Dewi Fitriani Dewi Fitriani (Bunayya, 2017)
Art therapy is a process of therapy which is using art as the recovery tool. Art therapy focus solely on its therapeutic process not on the end result of art product. Art therapy directly connect with all development stages of a child. They are using their physic to express their affection/empathy or anger toward their surroundings. In the process, they are applying their cognitive knowledge to be able to transfer the suppressed emotions into the process of creating the art. Aceh received the worst impact of Tsunami 2004 compare to other places. Its education is destroyed not only its infrastructure but also its process. Young children is the most fragile victim who needs special treatment during the recovery process. All children experience trauma during their life, not only tsunami victim, although the traumatic level might differs from one to another. The use of art therapy is very helpful in the learning process. The use of art therapy will release â€œthe impedimentâ€ within the child to be able to better function in the society. The inclusion of art therapy within curriculum will ensure the usage.